Chapter Blockchain Applications in Cybersecurity - Gómez, Eneko (InTechOpen, 2019)
Blockchain has been widely known thanks to Bitcoin and the cryptocurrencies. In this chapter, we analyze different aspects that relate to the application of blockchain with techniques commonly used in the field of cybersecurity. Beginning by introducing the use of blockchain technology as a secure infrastructure, the document delves into how blockchain can be useful to achieve several security requirements, common to most applications. The document has been focused on some specific cybersecurity disciplines to maintain simplicity: backup and recovery, threat intelligence and content delivery networks. As illustrated, some projects and initiatives are in the process of joining these two fields to provide solutions to existing problems.